An equivalent additional damping approach to assess vehicle-bridge interaction for train-induced vibration of short-span railway bridges. (1st June 2019) - Yau, J.D.; Martínez-Rodrigo, M.D.; Doménech, A.
Highlights: Offer an equivalent additional damping method to include VBI effects for short-span rail bridges. Interpret the phenomenon of response reduction for short bridges considering VBI effects. Identify the key parameters governing the additional damping by analytical approach. Verify the proposed additional damping approach by parametric studies. Abstract: Constant moving load models are widely adopted in the dynamic analysis of railway bridges under moving trains. However, the use of this simple model may overestimate the resonant response of simply supported bridges if the vehicle-bridge interaction (VBI) effects are neglected, particularly for short spans. To account for the VBI effects, Eurocode 1 allows engineers to consider an additional amount of structural damping which depends on the bridge span. This method is the so-called Additional Damping Method (ADM), and was formulated in order to provide a conservative prediction of the interaction benefit. Nevertheless, the Additional damping method may sometimes yield to an unsafe prediction of the bridge peak response. Considering the interaction benefits, an alternative analytical approach based on an equivalent VBI model under resonant excitations is presented in this investigation. The key parameters dominating the additional damping problem are subsequently identified. According to the numerical demonstrations supplied, the presented approach provides insights that enable an accurate prediction of the additional amount of damping needed in order to account for VBI effects on short simply-supported railway bridges.